A STRATEGY OF ADOPTING COLLABORATIVE TEACHING IN MATHEMATICS FOR HIGHER EDUCATION - Nurhazirah Mohamad Yunos; Set Foong Ng; Aishah Mahat; Ahmad Khudzairi Khalid; Norbaiti Tukiman, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Research has established collaborative teaching method as a means for educators to deliver instruction to students by performing collaborative practices among themselves or in the collaboration with industry experts. By collaboratively sharing their knowledge to students and applying different teaching techniques, students gain the benefits by learning from different educators and the industry expert. The collaborative teaching is a form of twenty-first century teaching method that benefits to both students and educators. However, there is still lack of research conducted that focuses on the full strategies to implement collaborative teaching in online distance learning (ODL) and face to face modes. Hence, this study aims to provide comprehensive strategies for adopting collaborative teaching in Mathematics subject for higher education in both ODL and face to face sessions. A qualitative technique was used to document the strategies of implementing collaborative teaching approach in class and to obtain feedback from educators and students regarding the implementation of collaborative teaching. The findings revealed that there were three phases adopted; pre collaborative teaching phase, collaborative teaching phase and post collaborative teaching phase. The effectiveness of the sessions depends on the planning in the pre collaborative teaching phase. It was shown that most students and educators had a positive impact on the collaborative teaching approach. This study can act as a reference for other educators to implement collaborative teaching strategies in their subject matter. In addition, it helps educators to have a better understanding of educators’ and students’ perceptions of adopting collaborative teaching.